Incorporating cardiopulmonary resuscitation training into a cardiac rehabilitation programme: A feasibility study. (1st February 2018) - Cartledge, Susie; Finn, Judith; Bray, Janet E; Case, Rosalind; Barker, Lauren; Missen, Diane; Shaw, James; Stub, Dion
Abstract: Background: Patients with a cardiac history are at future risk of cardiac events, including out-of-hospital cardiac arrest. Targeting cardiopulmonary resuscitation (CPR) training to family members of cardiac patients has long been advocated, but is an area in need of contemporary research evidence. An environment yet to be investigated for targeted training is cardiac rehabilitation. Aim: To evaluate the feasibility of providing CPR training in a cardiac rehabilitation programme among patients, their family members and staff. Methods: A prospective before and after study design was used. CPR training was delivered using video self-instruction CPR training kits, facilitated by a cardiac nurse. Data was collected pre-training, post-training and at one month. Results: Cardiac patient participation rates in CPR classes were high ( n = 56, 72.7% of eligible patients) with a further 27 family members attending training. Patients were predominantly male (60.2%), family members were predominantly female (81.5%), both with a mean age of 65 years. Confidence to perform CPR and willingness to use skills significantly increased post-training (both p <0.001). Post training participants demonstrated a mean compression rate of 112 beats/min and a mean depth of 48 mm. Training reach was doubled as participants shared the video self-instruction kit with a further 87 people. Patients, family members and cardiac rehabilitation staff had positive feedback about the training. Conclusions: We demonstrated that cardiac rehabilitation is an effective and feasible environment to provide CPR training. Using video self-instruction CPR training kits enabled further training reach to the target population.